Study on Microbiological Air Contamination: Poultry Houses (International Journal of Innovative Research in Computer Science & Technology, 2022)
Considering extensive poultry breeding is  followed by as comfortable as possible concentration of  birds within buildings, this exposes poultry house  personnel to increasing proportions to biological aerosol  that is mostly created by birds. A product that combines  with large concentrations of animals in constrained  locations is a significant source of bacterial air pollution,  which might pose a substantial health risk to humans.  Infective microbial or parasitic agents in fine particulate  matter may cause asthma, respiratory problems syndrome,  mucocutaneous irritation, respiratory problems, allergic  alveolitis natural dust toxic syndrome, including chronic  obstructive pulmonary disease. Organic pollution has been  linked to the aggravation of asthma, respiratory problems  symptoms, mucus irritation, especially chronic bronchitis.  Because the microbial air pollution national database for  poultry houses is currently insufficient, although  commercial broiler is on the rise, it is critical to collect,  analyze, as well as update current information.
Keywords: Allergic; Bacteria; Farming; Microbiological; Poultry